2021
DOI: 10.3354/esr01139
|View full text |Cite
|
Sign up to set email alerts
|

Marine distribution and foraging habitat highlight potential threats at sea for the Endangered Bermuda petrel Pterodroma cahow

Abstract: Marine spatial planning relies on detailed spatial information of marine areas to ensure effective conservation of species. To enhance our understanding of marine habitat use by the highly pelagic Bermuda petrel Pterodroma cahow, we deployed GPS tags on 6 chick-rearing adults in April 2019 and constructed a habitat suitability model using locations classified as foraging to explore functional responses to a selection of marine environmental variables. We defined 15 trips for 5 individuals, ranging from 1−6 tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 106 publications
2
6
0
Order By: Relevance
“…We analysed movement data, activity patterns and diving behaviour to quantify fine scale at-sea behaviours of incubating Bermuda petrels. Similar to previous studies [16, 31], GPS tracking showed that Bermuda petrels undertook extended foraging trips to the NNE of Bermuda, apparently targeting the path of the Gulf Stream, and confirming a reliance on vast oceanic areas for successful foraging as in other Pterodroma petrels [14, 16, 49, 50]. However, in contrast to many other Procellariiformes [10, 27], which can perform dives of considerable duration and depth (see references in [28, 51]), our TDR data suggest that the Bermuda petrel is a surface feeder with limited capacity to dive.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We analysed movement data, activity patterns and diving behaviour to quantify fine scale at-sea behaviours of incubating Bermuda petrels. Similar to previous studies [16, 31], GPS tracking showed that Bermuda petrels undertook extended foraging trips to the NNE of Bermuda, apparently targeting the path of the Gulf Stream, and confirming a reliance on vast oceanic areas for successful foraging as in other Pterodroma petrels [14, 16, 49, 50]. However, in contrast to many other Procellariiformes [10, 27], which can perform dives of considerable duration and depth (see references in [28, 51]), our TDR data suggest that the Bermuda petrel is a surface feeder with limited capacity to dive.…”
Section: Discussionsupporting
confidence: 93%
“…They were consistent in their departing direction from the colony, as has been observed in the Murphy's petrels (P. ultima) [49], showing a clear preference for the NNE (Fig. 1), targeting the Gulf Stream [16,31]. The pelagic area in which the "search" activity occurred (Fig.…”
Section: Foraging Trip Directions and Petrel At Sea Distribution Duri...supporting
confidence: 65%
See 1 more Smart Citation
“…Failed GPS fixes and the variable delay in achieving successful fixes (10-12 s max) result in inconsistent inter-point timing that is unusable for behavioral classification (see below; Patterson et al, 2008). Hence, trip points were interpolated to achieve consistent inter-point intervals of 2 h (3 h in 2019) by mathematically approximating the longitude and latitude of each point at these standardized times, given the assumption of a straight path between each GPS point (as in Raine et al, 2021). These interpolated data were used for all statistics, except for the calculations of total trip distance and trip duration, as the raw data gave more accurate estimations of these values.…”
Section: Analysis Of Gps Datamentioning
confidence: 99%
“…These versatile models can be fitted to tracking data and/or observational data from surveys together with environmental data to predict the occurrence (when distributional data are provided in presence-absence format) or abundance (when data are provided in absolute numbers) of seabirds as a function of the species’ ecological niche (e.g. Kruger et al 2018, Cleasby et al 2020, Raine et al 2021). SDMs can provide inference of distribution, occurrence, and abundance, the identification of areas of conservation priority, and threat assessments over large spatial and temporal scales, even though tracking and survey data are usually not spatially and temporally comprehensive (e.g.…”
Section: Introductionmentioning
confidence: 99%